Urgent need to expand syringe services programs in South Carolina and beyond - Quang Pham; Marc Burrows; Alain Litwin (BMC, 2022)
Abstract Opioid related overdose deaths in the United States claimed over 100,000 thousand lives during the 12-month period ending in April 2021, an increase of 28.5% from the previous period. Syringe services programs (SSPs) are an evidence-based harm reduction strategy that have been shown to be effective in reducing opioid overdose deaths and infectious complications and increasing rates of entry into recovery programs. Ignoring this evidence, South Carolina (SC) and several states have yet to legalize SSPs. In the absence of full legalization, the operation of SSPs in SC faces many barriers. Despite these barriers, Challenges Inc. has been successful in playing a critical role in preventing opioid overdoses through naloxone and fentanyl test strip distribution, reducing infectious complications by providing clean needles, treating individuals with hepatitis C and HIV, and helping patients remain in sustained recovery from opioids. In order for SSPs to function at their full potential to curb the rising tides of opioid overdose deaths and related health complications, policymakers in SC and similar states need to urgently legalize them.